Stay : a girl, a dog, a bucket list - Klise, Kate (Feiwel & Friends, an imprint of Macmillan Publishing Group, LLC, 2017)
Eli the dog has been with Astrid since she was a baby, and now that Eli is getting older and slowing down, Astrid wants to make fun memories with him, but knows what is most important to Eli is the time he spends with Astrid.